إشكالية التطوير الأكاديمي... ، وسبل التأسيس لنظام الجودة المطلوب، بكليات العلوم الإنسانية والاجتماعية بالجامعة الجزائرية - تغليت, صلاح الدين; مجبر واكلي, بديعة آيت (Sciences de l'Homme et de la Société; Vol. 19 (2016): SCIENCES DE L'HOMME ET DE LA SOCIÉTÉ, 2016)
تحتل العلوم الإنسانية والاجتماعية في الدول الحديثة مكانة مرموقة، فهي من ينظم الحياة الاجتماعية والسياسية والاقتصادية للأمم على اختلاف أمكنتها وأزمنتها، من هنا جاءت النظرة التخطيطية للعلوم الإنسانية والاجتماعية، وبيان أهميتها بالنسبة للفرد والمجتمع على حد سواء، وكان أن حتم هذا الواقع على  أمم كثيرة مراجعة منظوماتها التعليمية للعلوم الإنسانية والاجتماعية وتقيم أدائها ومنجزاتها والبحث في سبل تطويرها، وفي هذا السياق تتنافس الكليات على المستويين المحلي والعالمي بغية إحراز أفضل المراتب عبر تطوير وتنويع وسائل العمل وآلياته، والبحث في أنجع السبل وأيسرها لتجاوز المشكلات  المطروحة على الصعيدين الكمي والكيفي، والتأسيس لثقافة اقتصاد المعرفة من خلال تنمية وتطوير أدائها الأكاديمي ، ويلعب نظام إدارة الجودة الشاملة في كل هذا حدا فاصلا بين أنظمة قديمة باتت عاجزة عن الاستجابة لحاجيات العصر، ونظما مستحدثة تنسجم ومتغيرات الحياة المعاصرة. ومنه تأتي هذه الدراسة لتبحث في إشكالية التطوير الأكاديمي... ، وسبل التأسيس لنظام الجودة المطلوب ... ،بكليات العلوم الإنسانية والاجتماعية بالجامعة الجزائرية. Abstract : Social sciences and humanities in modern states Occupy a prominent place, they are that regulate the  social, political and economic life of nations despite  their variation in places, times and crises. From here came the planning- pragmatic approach for higher education in general  and humanities and social sciences in particular, showing  the statement of its importance for the individual and society alike, It was this fact that necessitated many nations to  review their educational systems related to Humanities and Social Sciences , assess their performance , achievements and research in the ways of developing them, in this context the  universities compete at the local and global levels in order to achieve the best ranks  through the development and diversification of the  work  means  and  it’smechanisms, research in the most effective way and the easiest one to overcome problems in both quantitative and qualitative sides, incorporate a culture of knowledge-based economy through the development of academic performance, in this way the total quality management system plays a border line between old systems being incapable of responding to the needs of the times, and innovative systems compatible with variables of contemporary life .From this point of view  comes this study to search in the Academic Development ... problematic, and ways of incorporation of the quality system required ...,  in the faculties of Humanities and Social Sciences in the Algerian university. مقدّمة: